2019
DOI: 10.3855/jidc.11048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of carbapenemase and mcr-1 genes in carbapenem-resistant Klebsiella pneumoniae isolates

Abstract: Introduction: Carbapenem-resistant Klebsiella pneumoniae are a major problem. We aimed to investigate carbapenemase-encoding genes and transferable mcr-1 genes among 57 carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates from hospitalized patients. Methodology: Antibiotic susceptibility tests were performed by Phoenix (BD). Results for ertapenem and colistin were confirmed by gradient diffusion and microdilution methods. Carbapenemase and mcr-1 genes were investigated by Polymerase Chain Reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 17 publications
1
28
1
1
Order By: Relevance
“…We detected two ST types, ST101 (95.6%) and ST147 (4.4%) in carbapenem and colistin resistant K. pneumoniae. In Turkey, a few study investigated mcr-1 to -3 genes among carbapenem and colistin resistant K. pneumoniae isolates and only Arabacı et al, determined mcr-1 positive KRCP (5.2%) [44,[51][52][53]. In this study, we investigated mcr-1 to -8 genes in colistin and carbapenem resistant K. pneumoniae and reported the molecular characteristics of mcr-1 positive CRKP.…”
Section: Discussionmentioning
confidence: 88%
“…We detected two ST types, ST101 (95.6%) and ST147 (4.4%) in carbapenem and colistin resistant K. pneumoniae. In Turkey, a few study investigated mcr-1 to -3 genes among carbapenem and colistin resistant K. pneumoniae isolates and only Arabacı et al, determined mcr-1 positive KRCP (5.2%) [44,[51][52][53]. In this study, we investigated mcr-1 to -8 genes in colistin and carbapenem resistant K. pneumoniae and reported the molecular characteristics of mcr-1 positive CRKP.…”
Section: Discussionmentioning
confidence: 88%
“…OXA-48 was reported to have lower activity against carbapenem but, showed increased activity when it co-exists with ESBLs 19 . Our result showed that OXA-48 was coupled with ESBLs in most isolates (Figure 4), which supports their resistance to carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…After sample collection, bacteria were cultured, followed by DNA extraction, gene amplification and whole-genome sequencing. For antibiotic susceptibility tests (AST), most studies employed the broth microdilution method (BMD) to determine colistin resistance 19,22,[50][51][52] . The genomic sequences were also used to identify carbapenemases and colistin resistance mechanisms, as well as assign sequence types (ST) of clones based on multi-locus sequence typing (MLST) 53 .…”
Section: Collection and Characterization Of Isolates In Included Studiesmentioning
confidence: 99%
“…As of now, ten different mcr variants noted from mcr-1 to mcr-10 have been described (6)(7)(8). Of more concern, coexistence of mcr and carbapenemase genes has been sporadically reported (9). For instance, mcr-1, mcr-3.5, and bla NDM−5 are found in an Escherichia coli isolate (10), mcr-4.3 and bla NDM−1 are co-identi ed in a clinical E. cloacae isolate from China (11), and bla VIM−4 and mcr-9 are found in an E. hormaechei isolate in USA (12).…”
Section: Introductionmentioning
confidence: 99%